Protocol for a patient-derived preclinical platform to model tumor-immune interactions and evaluate therapeutic efficacy - Wen-Hsin Chang; Andrew I. Chin; Ching-Hsien Chen (STAR Protocols)
Summary: Here, we present a protocol for a preclinical ex vivo platform combining experimental flexibility with preservation of the tumor microenvironment. We outline steps for isolating human peripheral blood mononuclear cells (PBMCs), preparing patient-derived precision-cut tumor slices (PCTSs), cryopreserving the samples, and setting up the co-culture system. We provide instructions for treatment applications, interactions, and analyzing therapy responses. By preserving tumor architecture and heterogeneity, this model is applicable for evaluating tumor characteristics, immune interactions, and treatment efficacy in translational cancer research. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.